2020
DOI: 10.1186/s12870-020-02640-9
|View full text |Cite
|
Sign up to set email alerts
|

Control of Panama disease of banana by intercropping with Chinese chive (Allium tuberosum Rottler): cultivar differences

Abstract: Panama disease (Fusarium wilt disease) caused by Fusarium oxysporum f. sp. cubense race 4 (FOC) severely threatens banana (Musa spp.) production worldwide. Intercropping of banana with Allium plants has shown a potential to reduce Panama disease. In this study, six cultivars of Chinese chive (Allium tuberosum Rottler) were selected to compare their differences in antifungal activity and active compounds. Three cultivars Duokang Fujiu 11, Fujiuhuang 2, and Duokang Sijiqing with higher levels of antifungal compo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Fusarium infections are suppressed with fungicides, the use of resistant cultivars, and the intercropping of Allium spp., which is considered an effective method of Fusarium biological control [ 6 , 7 ]. It has been shown that Fusarium growth can be suppressed by antifungal volatiles such as 2-methyl-2-pentenal and organosulfur compounds and non-volatiles such as spirostanol, furostanol, and steroidal saponins produced by Allium roots [ 8 , 9 , 10 , 11 , 12 ], as well as by Flavobacterium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium infections are suppressed with fungicides, the use of resistant cultivars, and the intercropping of Allium spp., which is considered an effective method of Fusarium biological control [ 6 , 7 ]. It has been shown that Fusarium growth can be suppressed by antifungal volatiles such as 2-methyl-2-pentenal and organosulfur compounds and non-volatiles such as spirostanol, furostanol, and steroidal saponins produced by Allium roots [ 8 , 9 , 10 , 11 , 12 ], as well as by Flavobacterium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Given the serious threats posed by FWB, effective prevention and control methods for the development of the banana industry around the world have become crucial. At present, soil fumigation, strategic crop rotation (Li et al, 2020 ), selection and breeding of varieties which are disease-resistant varieties (Xu et al, 2017 ; Huang et al, 2023 ), application of chemicals (Guo et al, 2013 ), biological control (Wang et al, 2013 ), and other methods are used to restrain FWB in China and other countries. However, the chlamydospores of FWB can persist in the soil for many years, limiting the effectiveness of crop rotation control.…”
Section: Introductionmentioning
confidence: 99%
“…Crop rotation and intercropping have been used to reduce the infections and inoculum levels ( Nadarajah et al, 2016 ). In China, farmers have been growing bananas in the presence of TR4 by rotating or intercropping with Chinese leek ( Allium tuberosum ; Nadarajah et al, 2016 ; Li et al, 2020a , b ). The most effective solution supporting continued production of bananas in infested soils would be replacing susceptible cultivars with resistant ones.…”
Section: Introductionmentioning
confidence: 99%